Emphasizing unique strengths and eliminating redundancy for research in low‐income and middle‐income countries: Lessons from a South American country. Issue 16 (22nd April 2015) - Burotto, Mauricio; Prasad, Vinay
<x xml:space="preserve">Abstract</x> Although low‐ and middle‐income countries face countless challenges that high‐income countries do not, they still manage to make funding available for biomedical research and discovery. These nations must conduct research preferentially based on original work and avoid replicative research.